Dual optical detection of a novel selective mercury sensor based on 7-nitrobenzo-2-oxa-1,3-diazolyl subunits - Wanichacheva N. (2014)
A novel macromolecule based on 2-[3-(2-aminoethylthio)propylthio]ethanamine covalently bound to two 7-nitrobenzo-2-oxa-1,3-diazolyl moieties was prepared as a fluoroionophore and a chromophore for the selective optical detection of Hg2+. The sensor was prepared in two steps and its fluoroionophoric and chromophoric properties toward various transition metal, alkali, and alkali earth cations were investigated. Compound 4 selectively binds Hg2+, and the binding is indicated by both fluorescence quenching and a chromogenic change which can be detected by the naked eye. In an 80:20 acetonitrile/water solvent mixture, 4 acts as an ON-OFF fluorescence switch upon Hg2+ binding, exhibiting efficient quenching and a detection limit of 10-7 M or 20 ppb. © 2009 Elsevier Ltd. All rights reserved.